A Metaphysics of Psychopathology - Zachar, Peter (Book collections on Project MUSE., 2014)
In this study Peter Zachar considers such terms as 'real' and 'reality' - invoked in psychiatry but often obscure and remote from their instances - as abstract philosophical concepts. He then examines the implications of his approach for psychiatric classification and psychopathology. Proposing what he calls a scientifically inspired pragmatism, Zachar considers such topics as the essentialist bias, diagnostic literalism, and the concepts of natural kind and social construct.